Habilidades matemáticas y verbales: diferencias de género en una muestra de 6º de Primaria y 1º de E.S.O. - Pomar Tojo, Carmen; Díaz Fernández, Olga; FERNÁNDEZ BARREIROS, Miriam; Sánchez Castaño, Teresa (FAISCA: Journal of High Abilities, 2011)
The variety of approaches in finding the differences between men and women and boys and girls has been a topic of interest for the different branches of learning throughout time. The social, educational and political situation in several countries is one of the many reasons why this topic has not lost its importance or is still relevant today. The results from several researches ascertain differences in behavioral manifestations and in different fields of knowledge between both males and females. In trying to discover the causes of this the research is continually resorting to biological, social, cultural and educational factors. The present study has been carried out with a simple of 505 subjects, 306 boys and 199 girls from 6º de Primaria and 1º de la E.S.O (Middle School). This sample was selected in more than 150 schools in Galicia, Spain to assist with a test that was given in conjuncture in mathematics with the objective of participating in a program for Stimulation of Mathematical Talent (ESTALMAT-GALICIA) in the Faculty of Mathematics at the University of Santiago de Compostela (USC). The instrument used was the PMA. The results point out that taking into consideration the whole sample, there are no significant differences in regards to the execution of the PMA factors between boys and girls. The only significant differences were in the numerical and reasoning factors. A more comprehensive analysis was done in those samples that scored above a 95 percentile and the results were very similar.
Keywords: Gender differences; Math abilities